PENGARUH BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - TITIN HARTINI TITIN (I-Finance Journal, 2016)
The development islamic banking from year to year continues to increase. This is evidenced by the financial performance of Islamic banks continue to increase from year to year where the financial performance measurement is calculated using ratio analysis. An assessment of the bank's financial performance in efficiency and productivity levels are conducted regularly on the basis of management reports and financial statements that are mirror achievement. This study was to determine the influence of operating expenses and operating income (ROA) to profitability Islamic Banking from 2012 to 2014 year. This study uses data time series over the past three years, so that the population in this study as well as a sample research. choosing samples used sampling technique in which non-probability selection carried out by a sampling method that is saturated sampling technique when all members of the population used as a sample. BOPO results showed a significant negative effect on profiabilitas Islamic banking in Indonesia because of the results obtained regression coefficient of -0075 showing the negative direction so BOPO negative effect on ROA and the significant value of 0.000 means that less than 0.05. Due to the significance level of less than 0.05 and the t (-4.371) <t table (1.690).So in this case a significant effect on profitability BOPO. It concluded that BOPO BOPO negative influence on ROA is because the higher the ROA reflects the lack of ability of banks to suppress operational expenses and increase operational revenue shortfalls resulting profit bank that in turn will lower ROA.Key Word: BOPO and Profitability